The Dual Burden of Air Pollution During Pregnancy: A Systematic Review of Physical and Psychological Consequences - Sakineh Raeisi; Ali Mirbalouchzehi; Mehran Yazdandoust (Journal of Environmental Health and Sustainable Development, 2025)
Introduction: Air pollution affects pregnant women and fetuses, leading to health complications. It increases risks like low birth weight, preterm labor and hypertension. Moreover, mental health issues such as depression and autism spectrum disorders may arise. Materials and Methods: This systematic review was conducted by examining data from four databases, including Google Scholar, PubMed, Web of Science, and Scopus covering the period from 2020 to 2024. The keywords used included "air pollution," "pregnant women," "fetal health," "pregnancy complications," "particulate matter," and "mental health". Using specific criteria, 109 studies were found. After excluding unrelated articles, 63 studies were analyzedand key information was extracted. Results: Air pollution significantly affects the physical and mental health of pregnant women. It increases the risk of depression, anxiety and autism spectrum disorders, with PM2.5 and NO2 being major contributors. Physical complications like preterm labor, gestational diabetes, miscarriage and preeclampsia are strongly linked to pollution. Lower-income women face higher exposure and mental health risks due to socioeconomic factors. Furthermore, living in urban areas and near pollution sources elevates health risks for mothers and fetuses. The second and third trimesters are the most vulnerable periods, highlighting the need for effective interventions. Conclusion: Air pollution severely affects the physical and mental health of pregnant women and fetuses, especially during the second and third trimesters. Preventive measures like air quality improvement and policy-making are crucial to protect maternal and fetal health.